Positive electrode material, positive plate and battery
By covering the rare earth metal phosphate compounds on the surface of the lithium ion battery positive material, it solves the problem of the structure and interface instability of the positive pole material under high -voltage and high -pressure and high -voltage conditions. promote.
Patent Information
- Application Number
- CN202411479481.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The existing lithium-ion battery positive electrode materials have serious structural and interface instability problems under high voltage and high temperature and high pressure conditions, resulting in significant deterioration in the storage and cycling performance of the battery.
By covering the coated materials that include rare earth metal phosphoric acid compounds on the surface of the substrate, the thickness ratio of the thickness of the coating layer to the weight of the rare earth metal element is controlled, and the capacity of the positive pole material and the high temperature cycle performance of the battery and the storage performance.
It achieves high stability of the surface/interface structure of the cathode material, reduces the impedance of the battery, improves the rate performance and high temperature performance of the battery, and extends the cycle life of the battery.
Smart Images

Figure CN119361640A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode material and a positive electrode sheet and a battery comprising the positive electrode material. Background Art
[0002] Lithium-ion batteries (LIBs) are considered the most promising candidate energy storage materials for portable electronics, power tools, and hybrid / all-electric vehicles due to their high energy density and long cycle life. In order to meet the requirements of social development, it is urgent to seek a lithium-ion battery with higher energy density and higher power density. This requires the cathode material used to have a higher specific capacity and a higher voltage platform. In theory, increasing the charging voltage can increase the Li + The effective utilization rate of Li + Excessive deintercalation in the layered structure will cause serious structural and interfacial instability problems in the cathode materials. Summary of the invention
[0003] The current commercial lithium-ion battery cathode materials mainly include lithium cobalt oxide, ternary materials, lithium manganese oxide, etc. These materials have serious structural and interface instability problems under high voltage. Among them, when lithium cobalt oxide is charged to above 4.5V, an irreversible phase transition from O3 to H1-3 will occur, accompanied by a large amount of slip between the Co-O-Co layers, which will cause partial surface structural collapse of lithium cobalt oxide and cracks in lithium cobalt oxide particles. At the same time, severe surface structural collapse will aggravate O loss and Co dissolution under high pressure, causing this structural collapse to spread to the core of lithium cobalt oxide particles, resulting in irreversible capacity loss of lithium cobalt oxide; similarly, ternary materials have Ni 4+ Due to the high oxidizability, side reactions are very likely to occur on the surface of the ternary material, which intensifies the interface phase change, forms a salt rock phase on the surface, increases the interface impedance, and causes the battery's electrical performance to decay; lithium manganese oxide undergoes a disproportionation reaction at high voltage (for example, above 4.5V) and is accompanied by an irreversible phase change to produce a non-electrochemically active phase, resulting in active lithium loss. These failure processes will be accelerated under high temperature and / or high pressure conditions, resulting in a significant deterioration in high temperature cycling and high temperature storage performance. Therefore, improving the high temperature and high pressure performance of the positive electrode material requires achieving high stability of the surface / interface structure of the positive electrode material.
[0004] In order to solve the above technical problems, surface coating is usually used in the prior art to slow down the structural degradation of the positive electrode material, thereby improving the high temperature and high pressure performance of the positive electrode material. For example, the ternary positive electrode material is modified by coating with rare earth oxides, and the multi-electron characteristics of rare earth elements are used to inhibit the release of lattice oxygen and surface phase transformation. However, this rare earth oxide coating layer is a lithium ion insulator and only plays a physical protective role. Its lithium ion transport capacity is low and the crystal structure is closed, resulting in limited modification effect, so that the rate performance of the battery of the coated modified ternary positive electrode material is poor; the lithium-rich manganese-based material is modified by coating with rare earth phosphates. Since the lithium-rich manganese-based material is a micron secondary spherical particle formed by the agglomeration of primary particles, the surface is uneven and there are many pores. The lithium-rich manganese-based material has a large specific surface area, high cost and it is difficult to achieve uniform coating of each primary particle, and this uneven coating is difficult to play a role in stabilizing the interface structure.
[0005] In order to overcome the technical problem that the serious interface and bulk structure degradation of the positive electrode material under high pressure in the charging and discharging process causes the storage performance and cycle performance of the battery to deteriorate significantly under high temperature and high pressure in the prior art, the present invention provides a positive electrode material and a positive electrode sheet and a battery comprising the positive electrode material. The positive electrode material of the present invention increases the capacity of the positive electrode material and the high temperature cycle performance and high temperature storage performance of the battery by coating a coating material including a rare earth metal phosphate compound on the surface of the substrate, and at the same time, by controlling the ratio of the thickness of the coating layer to the weight content of the rare earth metal element in the coating layer, the diffusion rate of the active ions near the surface of the positive electrode material can be increased, and the polarization generated by the positive electrode material during the charging and discharging process can be reduced, thereby improving the gram capacity of the battery, reducing the impedance of the battery and improving the rate performance of the battery.
[0006] The first aspect of the present invention provides a positive electrode material, wherein the positive electrode material comprises a substrate and a coating layer, the substrate comprises one or more of lithium cobalt oxide, a ternary material and lithium manganese oxide; the coating layer comprises a coating material, and the coating material comprises a chemical formula of RE x P y O z A rare earth metal phosphate compound, wherein 3x+5y=2z, 0<x≤1, 0<y≤1, RE includes one or more of Sc, Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu; the thickness of the coating layer is A, in nm, and based on the total weight of the positive electrode material, the weight content of RE in the rare earth metal phosphate compound is B wt%, then the positive electrode material satisfies the following relationship: 10≤A / B≤30.
[0007] A second aspect of the present invention provides a positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer located on one side or both sides of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode material described in the first aspect of the present invention.
[0008] The third invention of the present invention provides a battery, the battery comprising a negative electrode sheet and a positive electrode sheet, wherein the positive electrode sheet comprises the positive electrode material described in the first aspect of the present invention and / or the positive electrode sheet is the positive electrode sheet described in the second invention of the present invention, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer located on one side or both sides of the surface of the negative electrode current collector, the negative electrode active material layer comprises a negative electrode material, and the negative electrode material comprises one or more of a silicon-based material, a carbon-based material and a silicon-carbon composite material. Preferably, the negative electrode material is a silicon-carbon composite material.
[0009] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:
[0010] The surface of the positive electrode material of the present invention has a coating layer including a rare earth metal phosphate compound. On the one hand, the coating layer includes the rare earth metal phosphate compound. The rare earth metal phosphate compound has a high intrinsic thermal expansion coefficient, and the strong covalent interaction between the phosphate radical and the rare earth metal ion can effectively enhance the thermal stability of the coating material, so that the substrate still maintains a high structural stability under high temperature and high pressure, thereby achieving high stability of the surface / interface structure of the positive electrode material. At the same time, the RE-O bond energy in the rare earth metal phosphate compound can enhance the oxygen binding ability and the covalent effect generated by the hybridization of a large number of 4f electrons of the rare earth metal element and the 2p orbital of the O element, which can maintain the stability of the lattice oxygen and further enhance the interface structure of the substrate. The rare earth metal phosphate compound is a lithium ion conductor, which can accelerate the transmission of lithium ions at the interface of the positive electrode material, thereby reducing the impedance of the positive electrode sheet during high-temperature storage and high-temperature cycling, and reducing the irreversible capacity loss; on the other hand, the coating layer blocks the direct contact between the substrate and the electrolyte in a physically isolated manner, thereby inhibiting the acidic HF formed in the electrolyte from corroding the substrate, and at the same time preventing the active transition metal ions in the substrate from dissolving (for example, Co 2+ , Mn 2+), improve the cycle stability of the positive electrode material, and the coating layer covers the substrate and prevents the substrate from having side reactions with the electrolyte, thereby inhibiting the oxidative decomposition of the electrolyte and the occurrence of interface side reactions between the substrate and the electrolyte, thereby improving the cycle stability of the battery during the charge and discharge process and reducing irreversible capacity loss. At the same time, the present invention controls the relationship between the thickness of the coating layer and the weight content of the rare earth metal element in the coating layer, while achieving effective coating of the base material without hindering the diffusion of lithium ions, and even promoting the diffusion rate of lithium ions, and can also effectively inhibit the volume change of the positive electrode material during the cycle, so that the capacity of the positive electrode material, powder conductivity, cycle performance and high temperature performance are all improved.
[0011] Other features and advantages of the present invention will be described in detail in the following detailed description.
[0012] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 Shown is a SEM image of the positive electrode material based on lithium cobalt oxide of the present invention.
[0014] Figure 2a Shown is the EDS graph of the element Co in the positive electrode material in Example 1 of the present invention.
[0015] Figure 2b Shown is the EDS graph of element O in the positive electrode material in Example 1 of the present invention.
[0016] Figure 2c Shown is the EDS graph of element Y in the positive electrode material in Example 1 of the present invention.
[0017] Figure 2d Shown is the EDS graph of element P in the positive electrode material in Example 1 of the present invention.
[0018] Figure 3 Shown is the XRD pattern of the positive electrode material in Example 1 of the present invention.
[0019] Figure 4 Shown is the TG curve of the positive electrode material in Example 1 of the present invention. DETAILED DESCRIPTION
[0020] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention and are not used to limit the present invention. In this article, unless otherwise specified, the data range includes the endpoints.
[0021] It should be noted that the numerical expressions such as "first" and "second" in the present disclosure are only used to distinguish different substances or usage methods, and do not represent the difference in order.
[0022] The first aspect of the present invention provides a positive electrode material, wherein the positive electrode material comprises a substrate and a coating layer, the substrate comprises one or more of lithium cobalt oxide, a ternary material and lithium manganese oxide; the coating layer comprises a coating material, and the coating material comprises a chemical formula of RE x P y O z A rare earth metal phosphate compound, wherein 3x+5y=2z, 0<x≤1 (for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1), 0<y≤1 (for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1), RE includes one or more of Sc, Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu; the thickness of the coating layer is A, in nm, based on the total weight of the positive electrode material, the weight content of RE in the rare earth metal phosphate compound is B wt%, then the positive electrode material satisfies the following relationship: 10≤A / B≤30.
[0023] The coating material may include a rare earth metal phosphate compound, and the chemical formula of the rare earth metal phosphate compound may be RE x P y O z RE is a rare earth metal element. Figure 1 , Figure 2a , Figure 2b , Figure 2c and Figure 2d As shown, the rare earth metal phosphate compound may include a rare earth metal element RE, a phosphorus element P, and an oxygen element O. When RE includes one of Sc, Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, for example, RE is La, and x represents the number of La atoms; when RE includes multiple of Sc, Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, for example, RE is Sc and Y, and x represents the sum of the numbers of Sc atoms and Y atoms. In the chemical formula RE x P y Oz The relationship between the elements in the compound conforms to the principle that the algebraic sum of the positive and negative valences of the elements in the compound is zero.
[0024] The positive electrode material of the present invention comprises a coating structure of a rare earth metal phosphate compound. The rare earth metal phosphate compound has a high intrinsic thermal expansion coefficient. In a high-temperature working environment, the compressive stress generated by the rare earth metal phosphate compound on the main phase lattice can inhibit the generation and expansion of cracks in substrate particles, thereby achieving a toughening effect on the substrate particles, thereby effectively improving the problems of phase change and volume change of the substrate surface structure; and the RE-O bond in the rare earth metal element can enhance the oxygen binding ability, the covalent effect generated by the hybridization of a large number of 4f electrons of the rare earth metal element and the 2p orbital of the O element, and the phosphorus-oxygen double bond in the phosphate polyanion formed by the phosphorus element is very stable, which can further enhance the interface structure of the positive electrode material and improve the high-temperature storage and cycle performance of the positive electrode material under high voltage. However, when using rare earth metal phosphate compounds to coat the substrate, the inventors of the present invention found that it is difficult to effectively coat the substrate. If the content of rare earth metal phosphate compounds is too little, effective coating of the substrate cannot be achieved. If the content of rare earth metal phosphate compounds is too high, segregation will form a second phase that accumulates along the boundaries between particles, resulting in structural defects such as interface dislocations, which damage the structural strength of the material and fail to stabilize the surface of the substrate. For this reason, the relationship between the thickness of the coating layer and the weight content of the rare earth metal element in the coating layer is controlled at the same time, so that the coating layer has a specific composition and structure, which can achieve effective coating of the substrate. Since rare earth metal phosphate compounds are ionic conductors, they will not hinder the diffusion of lithium ions, and can even increase the transmission speed of lithium ions. In addition, they can effectively inhibit the volume change of the positive electrode material during the cycle, thereby improving the capacity, powder conductivity, cycle performance and high temperature performance of the positive electrode material.
[0025] In the present invention, a coating layer including a rare earth metal phosphate compound is formed on the surface of the substrate, and the relationship between the thickness of the coating layer and the weight content of the rare earth metal element in the coating layer is controlled. Compared with the prior art, the positive electrode material can achieve higher gram capacity, higher powder conductivity, higher cycle performance and high temperature performance.
[0026] In one example, the coating material is a rare earth metal phosphate compound.
[0027] In one embodiment, RE includes one or more of Y, Sm, Ce, Nd, La, Sc and Lu. The rare earth metal phosphate compound (RE) formed by the rare earth elements x P y O z) belongs to the tetragonal system (unit cell edge length a=b≠c, angle between edges α=β=γ=90°), the space group is I41 / amd, the structure has tetragonal symmetry, the chain of corner-sharing structural units composed of tetrahedron (PO4) and dodecahedron (ReO8) is parallel to the unit cell c axis and connected together by the edges. These characteristics ensure that the phosphate compound formed by it has better structural stability and phase stability, which can effectively alleviate the formation of H1-3 phase transition and improve the stability of positive electrode materials above 4.55V. At the same time, the rare earth metal phosphate compound with ultra-low thermal conductivity formed by the above rare earth metal elements can effectively hinder the rapid heat exchange between the electrode and the electrolyte, thereby alleviating the serious surface side reactions between the positive electrode material and the electrolyte in the fully charged state, and further improving the structural stability of the positive electrode material at high temperature.
[0028] In one example, 20≤A / B≤25.
[0029] In one example, based on the total weight of the positive electrode material, the weight content B wt% of the rare earth metal element in the rare earth metal phosphate compound is 0.12 wt%-1.4 wt% (for example, 0.12 wt%, 0.15 wt%, 0.2 wt%, 0.5 wt%, 0.8 wt%, 1 wt%, 1.2 wt% or 1.4 wt%). It can be understood that when the rare earth metal element (RE) in the rare earth metal phosphate compound is one rare earth metal element, B wt% is the weight content of the rare earth metal element in the coating layer; when the rare earth metal element (RE) in the rare earth metal phosphate compound is multiple (≥2) rare earth metal elements, B wt% is the sum of the weight contents of all rare earth metal elements in the rare earth metal phosphate compound in the coating layer.
[0030] In the present invention, the content of the rare earth metal elements is tested by atomic absorption spectroscopy (ICP-OES). The ICP test process is as follows: weigh 0.1g of sample, add 5ml of hydrochloric acid, heat and digest, filter with filter paper, and rinse the filter paper with deionized water for more than three times to ensure that ions fully enter the filtrate and set the volume to 100ml, and then use ICP-OES to detect the content of rare earth metal elements.
[0031] In one example, based on the total weight of the positive electrode material, the weight content B wt % of the rare earth metal element in the rare earth metal phosphate compound is 0.15 wt %-0.65 wt %.
[0032] In one example, based on the total weight of the positive electrode material, the weight content of phosphorus in the rare earth metal phosphate compound is 0.01wt%-1wt% (for example, 0.01wt%, 0.05wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt% or 1wt%).
[0033] In one example, based on the total weight of the positive electrode material, the weight content of phosphorus in the rare earth metal phosphate compound is 0.02 wt %-0.5 wt %.
[0034] In one example, the thickness A nm of the coating layer is 2 nm-40 nm (e.g., 2 nm, 4 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm or 40 nm). In the present invention, the thickness of the coating layer refers to the interval formed by the thickness of the thinnest part and the thickness of the thickest part of the coating layer.
[0035] In the invention, the thickness of the coating layer can be obtained by transmission electron microscopy (TEM) testing. Based on the different crystal structures and atomic masses of lithium cobalt oxide and rare earth metal phosphate compounds, their image contrasts are different in TEM photos. The material with different outer layer contrasts in the image is the coating metal phosphate compound. In this way, the thickness of the corresponding coating layer can be obtained. In order to reduce the error, 2-10 pictures can be randomly selected to test the thickness of the corresponding coating layer, and the final thickness range is determined by taking the average value.
[0036] In one example, the coating layer has a thickness A nm of 3 nm to 17 nm.
[0037] In one example, based on the total weight of the positive electrode material, the weight content of the rare earth metal phosphate compound is 0.15wt%-4.5wt% (for example, 0.2wt%, 0.4wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt% or 4.5wt%).
[0038] In one example, based on the total weight of the positive electrode material, the weight content of the rare earth metal phosphate compound is 0.4 wt %-2 wt %.
[0039] In one example, the thickness A nm of the coating layer is 3 nm-17 nm, and the weight content of the rare earth metal phosphorus compound is 0.4 wt%-2 wt% based on the total weight of the positive electrode material. Controlling the coating thickness and the weight content of the rare earth metal phosphorus compound in the coating layer within the above range can promote lithium ion transmission between the coating layer and the substrate interface, thereby improving the stability of the positive electrode material without reducing the discharge capacity of the positive electrode material.
[0040] In one example, the XRD spectrum of the positive electrode material has a characteristic peak in the range of 2θ=25°-30° (e.g., 25°, 26°, 27°, 28°, 29° or 30°). The characteristic peak in the range of 2θ=25°-30° indicates that the positive electrode material has a chemical formula of RE x P y O z In the presence of rare earth metal phosphate compounds, the positive electrode material has higher structural stability.
[0041] In one example, the thermogravimetric curve of the positive electrode material has a weight loss step in the range of 620°C-900°C (e.g., 620°C, 650°C, 700°C, 750°C, 800°C, 850°C or 900°C). The presence of a thermogravimetric step in the range of 620°C-900°C indicates that thermal decomposition occurs in the range of 620°C-900°C, and the positive electrode material undergoes thermal decomposition at such a high temperature, indicating that the thermal stability of the positive electrode material is relatively high.
[0042] In one example, the weight loss step has a weight loss range of 0.05%-2% (eg, 0.05%, 0.5%, 1%, 1.5% or 2%).
[0043] In the present invention, the weight loss range represents the difference between the mass of the position where the mass decreases in the weight loss step starts and the minimum mass in the weight loss step, wherein the mass of the position where the mass decreases in the weight loss step starts represents the mass corresponding to the position where the mass decreases by at least 0.05wt% compared to when the mass is not decreased.
[0044] In one example, the weight loss range of the weight loss step is 0.1%-0.5%.
[0045] In one example, the XRD spectrum of the positive electrode material has a characteristic peak in the range of 2θ=25°-30°, and the thermogravimetric curve of the positive electrode material has a weight loss step in the range of 620° C.-900° C. At this time, the positive electrode material has a stable structure and high thermal stability, especially high high-temperature structural stability.
[0046] In one example, the substrate is a single crystal structure. When the substrate is a single crystal structure, the substrate has fewer surface defects, a lower specific surface area and non-boundary properties, and the coating layer is more tightly combined with the substrate, and the positive electrode material has a higher structural stability.
[0047] In one example, the median particle size Dv50 of the substrate is 2 μm-18 μm (e.g., 3 μm, 5 μm, 8 μm, 10 μm, 13 μm, 15 μm or 18 μm). By controlling the median particle size Dv50 of the substrate within the above range, the median particle size of the positive electrode material can be controlled within an appropriate range, thereby improving the compaction density of the positive electrode sheet and the rate performance of the battery.
[0048] In one example, the median particle size Dv50 of the substrate is 3 μm-6 μm.
[0049] In the present invention, the median particle size Dv50 is the particle size at which the cumulative distribution of particle volume is 50%. The median particle size can be obtained by testing with a Malvern 3000 laser particle size analyzer.
[0050] In one example, the average sphericity of the substrate is 0.6-1 (e.g., 0.6, 0.7, 0.8, 0.9 or 1). Within this range, the particles of the positive electrode material have a good spherical profile, which can improve the powder fluidity of the positive electrode material in the process of processing into a positive electrode sheet and reduce the processing difficulty. On the other hand, it is conducive to the uniform dispersion of the positive electrode conductive agent and the positive electrode binder on the surface of the positive electrode material, thereby promoting the current density distribution of the positive electrode material during the battery charging and discharging process, making the distribution of the micro stress generated by lithium insertion and extraction more uniform, thereby improving the structural stability of the positive electrode material during the battery cycle, thereby improving the battery cycle stability.
[0051] In one example, the average sphericity of the substrate is 0.7-1.
[0052] In one example, the substrate is a single crystal structure, and the average sphericity of the substrate is 0.7-1.
[0053] In the present invention, the average sphericity refers to the degree to which the particle shape is close to a sphere, which can be measured by Microtrac S3500SI laser particle size and shape analyzer.
[0054] In one example, the substrate has a single crystal structure, a median particle size Dv50 of the substrate is 3 μm-6 μm, and an average sphericity of the substrate is 0.7-1.
[0055] In one example, the ternary material includes lithium nickel cobalt manganese oxide and / or lithium nickel cobalt aluminum oxide.
[0056] In one example, the positive electrode material can be prepared by the following method: mixing the substrate with a rare earth metal nitrate compound and a phosphoric acid compound in a first solvent, reacting for a certain period of time to obtain a first product, and calcining the first product at high temperature. The positive electrode material prepared by the above method has a tight bond between the substrate and the coating layer, and the structural stability of the positive electrode material, especially the structural stability under high temperature and high pressure, is higher.
[0057] In one example, the first solvent includes deionized water and / or ethanol.
[0058] In one example, the molar ratio of the substrate, the rare earth metal ions in the rare earth metal nitrate compound, and the phosphate ions in the phosphate compound is 1:(0.001-0.02):(0.001-0.02) (for example, 1:0.001:0.001, 1:0.005:0.001, 1:0.01:0.005, 1:0.002:0.002, 1:0.005:0.005, 1:0.008:0.001, 1:0.005:0.008, 1:0.01:0.015, 1:0.02:0.015, or 1:0.015:0.02).
[0059] In one example, the molar ratio of the substrate, the rare earth metal ions in the rare earth metal nitrate compound, and the phosphate ions in the phosphate compound is 1:(0.002-0.005):(0.002-0.005).
[0060] In the process of preparing the positive electrode material described in the present invention, it is difficult to control the thickness of the coating layer in the positive electrode material. In order to make the thickness of the coating layer in the prepared positive electrode material within an appropriate range, the present invention controls the thickness of the coating layer within an appropriate range by controlling the molar ratio of the substrate, the rare earth metal ions in the rare earth metal nitrate compound and the phosphate ions in the phosphate compound, thereby achieving the effect of increasing the transmission rate of lithium ions in the coating layer and reducing the volume expansion rate of the substrate, thereby improving the powder conductivity of the positive electrode material, reducing the impedance of the positive electrode sheet, and improving the high-temperature cycle stability and high-temperature storage performance of the battery.
[0061] In one example, the rare earth metal nitrate compound includes a nitrate compound of at least one of Sc, Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb or Lu.
[0062] In one example, the rare earth metal nitrate compound includes one or more of yttrium nitrate, samarium nitrate, cerium nitrate, neodymium nitrate, lanthanum nitrate, scandium nitrate, gadolinium nitrate and lutetium nitrate.
[0063] In one example, the phosphoric acid compound includes one or more of phosphoric acid, diammonium phosphate, and ammonium hydrogen phosphate.
[0064] In one example, the reaction time is not less than 1 h (eg, 1 h, 2 h, 3 h, 4 h, 5 h or 6 h).
[0065] In one example, the high temperature calcination conditions are: temperature of 200°C-600°C (for example, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C or 600°C), time of 2h-10h (for example, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h).
[0066] In one example, the high temperature calcination conditions are: temperature of 400° C.-500° C., and time of 4 h-6 h.
[0067] In one example, the high temperature calcination is performed in an air or oxygen atmosphere.
[0068] The second aspect of the present invention provides a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer located on one side or both sides of the positive electrode current collector, and the positive electrode active material layer comprises the positive electrode material described in the first aspect of the present invention.
[0069] The materials of the positive electrode sheet other than the positive electrode material can be prepared in accordance with methods in the art, and can achieve the effects of low impedance and high stability.
[0070] In one example, the median particle size Dv50 of the positive electrode material is 2 μm-18 μm. Controlling the median particle size of the substrate within the above range can make the positive electrode sheet have a higher compaction density and improve the rate performance of the battery.
[0071] In one example, the median particle size Dv50 of the positive electrode material is 3 μm-6 μm.
[0072] In one example, based on the total weight of the positive electrode active material layer, the weight content of the positive electrode material is 80 wt%-98.5 wt% (eg, 80 wt%, 85 wt%, 90 wt%, 95 wt% or 98.5 wt%).
[0073] In one example, based on the total weight of the positive electrode active material layer, the weight content of the positive electrode material is 88 wt %-97 wt %.
[0074] In one example, the positive electrode active material layer further includes a positive electrode conductor and a positive electrode binder.
[0075] In one example, based on the total weight of the positive electrode active material layer, the weight content of the positive electrode conductor is 0.6wt%-10wt% (for example, 0.6wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%), and the weight content of the positive electrode binder is in the range of 0.9wt%-10wt% (for example, 0.6wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%).
[0076] In one example, based on the total weight of the positive electrode active material layer, the weight content of the positive electrode conductor is 1.2 wt %-5 wt %, and the weight content of the positive electrode binder is in the range of 1.8 wt %-7 wt %.
[0077] In one example, the positive electrode conductive agent includes one or more of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes and metal powder.
[0078] In one example, the positive electrode binder includes one or more of sodium carboxymethyl cellulose, styrene-butadiene latex, polytetrafluoroethylene, polyvinylidene fluoride (PVDF), and polyethylene oxide.
[0079] In one embodiment, the surface density of the positive electrode sheet is 5 g / cm 2 20g / cm 2 (For example, 5g / cm 2 , 6g / cm 2 , 7g / cm 2 , 8g / cm 2 , 9g / cm 2 , 10g / cm 2 , 11g / cm 2 , 12g / cm 2 , 13g / cm 2 , 14g / cm 2 , 15g / cm 2 , 16g / cm 2 , 18g / cm 2 or 20g / cm 2 ). The surface density of the positive electrode sheet is controlled within the above range. At this time, the positive electrode sheet has a higher mass load of the positive electrode material, which can improve the energy density of the battery.
[0080] In the present invention, the surface density of the positive electrode sheet refers to the surface density of the positive electrode active material layer on one side of the positive electrode sheet. When there is a positive electrode active material layer on one side of the positive current collector, the surface density of the positive electrode sheet is the surface density of the positive electrode active material layer on that side; when there are positive electrode active material layers on both sides of the positive current collector, the surface densities of the positive electrode active material layers on both sides of the positive electrode sheet are the same, and the surface density of the positive electrode sheet is the surface density of the positive electrode active material layer on one side.
[0081] In one embodiment, the surface density of the positive electrode sheet is 7 g / cm 2 -18g / cm 2 .
[0082] In one example, the compaction density of the positive electrode sheet is 3.5 g / cm 3 -4.5g / cm 3 (For example, 3.5 g / cm 3 、3.6g / cm 3 、3.7g / cm 3 、3.8g / cm 3 、3.9g / cm 3 , 4g / cm 3 , 4.1g / cm 3 , 4.2g / cm 3 , 4.3g / cm 3 4.4g / cm 3 or 4.5g / cm 3 ). By controlling the compaction density of the positive electrode sheet within the above range, the positive electrode sheet can have both a higher electrode porosity and a higher compaction density, thereby making the battery have a higher energy density.
[0083] In the present invention, the compaction density of the positive electrode sheet refers to the compaction density of the positive electrode active material layer on one or both sides of the positive electrode sheet. When there is a positive electrode active material layer on one side of the positive current collector, the compaction density of the positive electrode sheet is the compaction density of the positive electrode active material layer on that side; when there are positive electrode active material layers on both sides of the positive current collector, the compaction density of the positive electrode active material layers on both sides of the positive electrode sheet is the same, and the compaction density of the positive electrode sheet is the compaction density of the positive electrode active material layer on one side.
[0084] In one example, the compaction density of the positive electrode sheet is 4 g / cm 3 -4.2g / cm 3 .
[0085] In one example, the thickness of the positive electrode sheet is 0.03 mm-0.1 mm. In the present invention, the thickness of the positive electrode sheet is the overall thickness of the positive electrode sheet, which is the sum of the thickness of the positive electrode current collector and the thickness of the positive electrode active material layer.
[0086] Since the positive electrode sheet includes the positive electrode material of the present invention, the impedance of the positive electrode sheet is reduced and the high-temperature structural stability is improved.
[0087] The third aspect of the present invention provides a battery, comprising a negative electrode sheet and a positive electrode sheet, wherein the positive electrode sheet comprises the positive electrode material described in the first aspect of the present invention and / or the positive electrode sheet is the positive electrode sheet described in the second aspect of the present invention, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer located on one side or both sides of the surface of the negative electrode current collector, the negative electrode active material layer comprises a negative electrode material, and the negative electrode material comprises one or more of a silicon-based material, a carbon-based material and a silicon-carbon composite material.
[0088] In one example, the negative electrode material is a silicon-carbon composite material.
[0089] In one example, based on the total weight of the negative electrode active material layer, the weight content of silicon element is 1.5wt%-50wt% (for example, 1.5wt%, 2wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt% or 50wt%).
[0090] In one example, based on the total weight of the negative electrode active material layer, the weight content of silicon is 3 wt %-20 wt %.
[0091] In one example, the average sphericity of the negative electrode material is 0.5-1 (eg, 0.5, 0.6, 0.7, 0.8, 0.9 or 1).
[0092] In one example, the average sphericity of the silicon-carbon composite material is 0.5-1 (e.g., 0.5, 0.6, 0.7, 0.8, 0.9 or 1). By controlling the average sphericity of the silicon-carbon composite material within the above range, the silicon-carbon composite material can be bonded to form a negative electrode material with a higher sphericity, thereby forming a good conductive network, accelerating the transmission of electrons, and thus improving the rate performance of the battery.
[0093] In one example, the negative electrode material is a silicon-carbon composite material, and based on the total weight of the negative electrode active material layer, the weight content of silicon is 1.5wt%-50wt%, and the average sphericity of the silicon-carbon composite material is 0.5-1. By controlling the average sphericity of the silicon-carbon composite material and the weight content of silicon in the negative electrode active material layer, on the one hand, the coating layer of the positive electrode material in the positive electrode sheet can effectively inhibit the crosstalk of the carbon dioxide gas generated by the negative electrode sheet during the high-temperature cycle to the substrate in the positive electrode material (crosstalk is the diffusion of the byproduct carbon dioxide gas generated by the negative electrode through the diaphragm to the positive electrode side, thereby inducing the LCO / NCM positive electrode phase change oxygen evolution on the surface of the positive electrode material, followed by a chemical reaction to generate CO2 and H2O, and releasing a large amount of heat to induce thermal runaway, causing the positive electrode material to fail faster), thereby effectively improving the safety performance of the battery; on the other hand, the coating layer of the positive electrode material can inhibit the dissolution of metal ions in the substrate (for example, cobalt ions, manganese ions), thereby reducing the deposition of dissolved metal ions in the negative electrode sheet, destroying the crystal structure of the silicon-carbon composite material, and accelerating the battery cycle failure at high temperature. Therefore, by combining the positive electrode material in the positive electrode sheet with the silicon-carbon composite material in the negative electrode sheet, the energy density, cycle stability, rate performance and safety performance of the battery can be improved.
[0094] In one example, the negative electrode active material layer further includes a negative electrode conductor and a negative electrode binder.
[0095] In one example, based on the total weight of the negative electrode active material layer, the weight content of the negative electrode material is 88wt%-98.5wt% (for example, 88wt%, 90wt%, 92wt%, 95wt% or 98.5wt%), the weight content of the negative electrode conductive agent is 0wt%-5wt% (for example, 0, 0.1wt%, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt% or 5wt%), and the weight content of the negative electrode binder is in the range of 1.5wt%-7wt% (for example, 1.5wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt% or 7wt%). When the weight content of the negative electrode conductive agent in the negative electrode active material layer is 0, it means that there is no negative electrode conductive agent in the negative electrode active material layer, and the negative electrode sheet still has the conductivity that meets the battery requirements.
[0096] In one example, based on the total weight of the negative electrode active material layer, the weight content of the negative electrode material is 90wt%-97.5wt%, the weight content of the negative electrode conductor is 0.5wt%-2.0wt%, and the weight content of the negative electrode binder is in the range of 2wt%-8wt%.
[0097] In one example, the negative electrode conductive agent includes one or more of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes and metal powder.
[0098] In one example, the negative electrode binder includes one or more of sodium carboxymethyl cellulose, styrene-butadiene latex, polytetrafluoroethylene and polyethylene oxide.
[0099] In one example, the battery is a lithium-ion battery.
[0100] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0101] The following examples are used to illustrate the positive electrode sheet and the negative electrode sheet of the present invention.
[0102] Example 1
[0103] (1) Preparation of positive electrode materials
[0104] The substrate (LiCoO2), the rare earth metal nitrate compound (yttrium nitrate) and the phosphoric acid compound (ammonium dihydrogen phosphate) are mixed in a first solvent (deionized water) at a molar ratio of 1:0.004:0.004, and the reaction time is 6 hours to obtain a first product;
[0105] After multiple washing and filtering, the first product was vacuum dried at 120°C for 12 hours and then high-temperature baked. The high-temperature baking conditions were: baking at 500°C in an air atmosphere for 6 hours to obtain yttrium phosphate-coated LiCoO2, whose molecular formula is LiCoO2@0.5%YPO4.
[0106] The median particle size Dv50 of the positive electrode material prepared above is 3.5±0.5μm, wherein the weight content of the rare earth metal phosphate compound in the positive electrode material is 1.05wt%, the weight content Bwt% of the rare earth metal element Y in the rare earth metal phosphate compound in the positive electrode material is 0.5wt%, and the thickness A of the coating layer is 10nm-12nm.
[0107] (2) Preparation of positive electrode
[0108] The prepared positive electrode material (LiCoO2@0.5% YPO4), positive electrode binder (PVDF), and positive electrode conductor (conductive carbon black) were mixed in a mass ratio of 97wt%:1.8wt%:1.2wt%, and dispersed in N-methylpyrrolidone, and stirred under the action of a vacuum mixer until the mixed system became a positive electrode active slurry with uniform fluidity, and the solid content in the slurry was 70wt%. The slurry was evenly coated on both sides of the 10μm positive electrode current collector (aluminum foil), vacuum dried, and compacted to 4.05g / cm by a roller press. 3 , and obtain the positive electrode.
[0109] (3) Preparation of negative electrode sheet
[0110] The negative electrode material includes one or more of silicon-based materials, carbon-based materials and silicon-carbon composite materials, wherein the mass percentages of negative electrode active material, conductive agent and negative electrode binder in the negative electrode coating are 95wt%: 1.5wt%: 3.5wt%. The above materials are mixed to form a negative electrode slurry to obtain a slurry with a viscosity of 3000mPa.s and a solid content of 52%. The negative electrode slurry is coated on both sides of a copper foil of 8μm, and then dried at a baking temperature of 100°C for 4h, and rolled to obtain a compacted density of 1.65g / cm 3 For details of the negative electrode sheet, please refer to Table 1-1 and Table 1-2.
[0111] in, Figure 3 is the XRD diagram of Example 1. Figure 3 It can be seen that the characteristic peak A is located at 28.5, that is, there is a characteristic peak in the range of 2θ=25°-30° in the XRD spectrum of the positive electrode material.
[0112] Figure 4 is the TG curve of Example 1, from Figure 4 It can be seen that the weight loss range of the weight loss step is 0.4%.
[0113] Example 2
[0114] The same method is carried out as in Example 1, except that multiple parameter values of the positive electrode material, the positive electrode sheet and the negative electrode sheet are changed to illustrate the effects of changes in multiple parameter values of the positive electrode material. For details, see Table 1-1 and Table 1-2.
[0115] Example 3
[0116] The same method is carried out as in Example 1, except that multiple parameter values of the positive electrode material, the positive electrode sheet and the negative electrode sheet are changed to illustrate the effects of changes in multiple parameter values of the positive electrode material. For details, see Table 1-1 and Table 1-2.
[0117] Example 4 Group
[0118] This group of embodiments is used to illustrate the impact when A / B changes.
[0119] This embodiment group is carried out with reference to embodiment 1, except that A / B is changed, see Table 1-1 and Table 1-2 for details.
[0120] Example 5 Group
[0121] This group of examples is used to illustrate the effects produced when the rare earth metal phosphate compound is changed.
[0122] This example group was carried out with reference to Example 1, except that the rare earth metal phosphate compound was changed, as shown in Table 1-1 and Table 1-2 for details.
[0123] Example 6 Group
[0124] This group of examples is used to illustrate the impact when the type of substrate changes.
[0125] This example group was carried out with reference to Example 1, except that the type of substrate was changed, as shown in Table 1-1 and Table 1-2 for details.
[0126] Example 7 Group
[0127] This group of examples is used to illustrate the effects produced when the crystal structure of the substrate changes.
[0128] This example group was carried out with reference to Example 6b, except that the crystal structure of the substrate was changed, as shown in Table 1-1 and Table 1-2 for details.
[0129] Example 8 Group
[0130] This set of examples is used to illustrate the effects produced when the average sphericity of the substrate is changed.
[0131] This example group was carried out with reference to Example 1, except that the average sphericity of the substrate was changed, as shown in Table 1-1 and Table 1-2.
[0132] Example 9 Group
[0133] This group of embodiments is used to illustrate the impact when the surface density of the positive electrode sheet changes.
[0134] This embodiment group is carried out with reference to the embodiment 1, except that the surface density of the positive electrode sheet is changed, as shown in Table 1-1 and Table 1-2 for details.
[0135] Example 10 Group
[0136] This group of embodiments is used to illustrate the influence produced when the weight content of silicon in the negative electrode active material layer changes.
[0137] This example group was carried out with reference to Example 1, except that the weight content of silicon in the negative electrode active material layer was changed, as shown in Table 1-1 and Table 1-2 for details.
[0138] Example 11 Group
[0139] This group of embodiments is used to illustrate the impact produced when the average sphericity of the negative electrode material changes.
[0140] This example group was carried out with reference to Example 1, except that the average sphericity of the negative electrode material was changed, as shown in Table 1-1 and Table 1-2 for details.
[0141] Example 12
[0142] The same method is carried out as in Example 1, except that the specific selection of the negative electrode material is changed. For details, see Table 1-1 and Table 1-2.
[0143] Comparative Example 1
[0144] The same method is carried out as in Example 1, except that the positive electrode material is adjusted to a substrate without a coating layer including a rare earth metal phosphate compound, as shown in Table 1-1 and Table 1-2 for details.
[0145] Comparative Example 2
[0146] The same procedure is carried out as in Example 1, except that A / B is changed by adjusting B wt%, as shown in Table 1-1 and Table 1-2 for details.
[0147] Comparative Example 3
[0148] The same is carried out as in Example 1, except that A / B is changed by adjusting A and B, as shown in Table 1-1 and Table 1-2 for details.
[0149] Table 1-1
[0150]
[0151]
[0152]
[0153] * indicates the same as in Example 1; - indicates absence.
[0154] Table 1-2
[0155]
[0156]
[0157] *Same as Example 1;
[0158] - means it does not exist.
[0159] Preparation Example
[0160] The positive electrode sheets and negative electrode sheets obtained in the examples and comparative examples were used to prepare batteries according to the following methods.
[0161] (1) Positive electrode
[0162] The positive electrode sheets obtained from the above embodiments and comparative examples are respectively used
[0163] (2) Negative electrode
[0164] The negative electrode sheets obtained in the above-mentioned embodiments and comparative examples were used respectively.
[0165] (3) Electrolyte
[0166] The electrolyte solution uses a 1 mol / L lithium hexafluorophosphate electrolyte, and the solvent of the electrolyte solution is a mixed solvent of ethylene carbonate: dimethyl carbonate: 1,2-propylene glycol carbonate in a volume ratio of 1:1:1.
[0167] (4) Diaphragm
[0168] The diaphragms used in the examples and comparative examples are rubber-coated diaphragms with polypropylene as the base material and ceramic coated on one side thereof.
[0169] (5) Preparation of lithium-ion batteries
[0170] The positive electrode sheet of step (1), the negative electrode sheet of step (2) and the separator of step (4) are stacked in the order of positive electrode sheet, separator and negative electrode sheet, and then wound to obtain a battery cell; the battery cell is placed in an outer packaging aluminum foil, the electrolyte of step (3) is injected into the outer packaging, and a lithium ion battery is obtained through vacuum packaging, standing, forming, shaping, sorting and other processes.
[0171] Test Case
[0172] The positive electrode materials, positive electrode sheets and lithium-ion batteries obtained in the examples and comparative examples were tested as follows:
[0173] 1. Test of gram capacity
[0174] The soft-pack batteries prepared in the examples and comparative examples were charged to 4.55 V at a rate of 0.1C at a test temperature of 25°C, and then discharged to 3 V at a rate of 0.1C. The discharge capacity was measured, and the gram capacity = discharge capacity / weight of the positive electrode material.
[0175] 2. Test of powder conductivity
[0176] The conductivity of the cathode material powder was tested by the four-probe method. The resistance of the powder under five pressure points of 1KN, 2KN, 3KN, 4KN and 5KN was tested respectively by the instrument, and then the conductivity and resistivity of the cathode material powder were automatically calculated by the computer. The data in Table 2 are the conductivity under 5KN pressure.
[0177] 3. Impedance (Rct) test
[0178] Impedance (Rct) is obtained through electrochemical impedance spectroscopy (EIS) testing, specifically, the soft-pack cells of the embodiments and comparative examples are tested using Shanghai Chenhua CHI600E electrochemical workstation, the battery state is adjusted to 50% SOC state, and the parameter distribution of the CHI600E electrochemical workstation is set as follows: the voltage window is set to 3-4.55V, the amplitude is 5mV, and the frequency range is 10-10Hz, and then the impedance (Rct) can be measured.
[0179] 4. Capacity retention rate test
[0180] The corresponding obtained battery was placed in a constant temperature environment of 45°C and subjected to charge and discharge cycle test at a rate of 1.2C / 0.5C within the charge and discharge cut-off voltage range (the cut-off voltage range is 3V to 4.55V), and the charge and discharge cycle was 500 times, specifically, charged at a rate of 1.2C to a cut-off voltage of 4.55V, and then discharged at a rate of 0.5C to a cut-off voltage of 3V. In addition, for the first cycle, the discharge capacity of the first cycle of the test was recorded as x mAh, and so on, the discharge capacity of the 500th cycle was calculated as y mAh; the discharge capacity of the 500th cycle was divided by the discharge capacity of the first cycle, and the 500th cycle capacity retention rate was obtained as R=y / x.
[0181] 5. Ratio test
[0182] The lithium ion batteries prepared in the examples and comparative examples were charged and discharged at a test temperature of 25°C and a test voltage range of 3.0V-4.55V. Specifically, they were charged at a charge rate of 0.7C to a cut-off voltage of 4.55V, and discharged at discharge rates of 0.2C, 0.5C, 0.7C, 1C, and 2C to a cut-off voltage of 3V. The discharge capacity retention rates at discharge rates of 0.2C / 0.7C / 2C relative to those at 0.2C were calculated. Taking 0.7C as an example, 0.5C capacity retention rate = 0.5C discharge capacity / 0.2C discharge capacity.
[0183] 6. 85℃ high temperature storage performance test
[0184] At 25°C, charge at 0.7C to 4.55V, then discharge at 0.2C to 3.0V, record the initial discharge capacity Q1, and then continue to charge to full charge, store in a constant temperature box at 85°C for 8H, take out the battery cell after the storage time, cool it back to room temperature, and then discharge at 0.2C, record the discharge capacity Q2 after storage, divide the discharge capacity Q2 after storage by the initial discharge capacity Q1 to get the residual capacity retention rate, that is, residual capacity retention rate = (Q2 / Q1)*100%.
[0185] The obtained results are recorded in Table 2.
[0186] Table 2
[0187]
[0188]
[0189] It can be seen from Table 2 that the specific capacity of the positive electrode material of the embodiment is improved through the comparative examples and the embodiments, and the powder conductivity of the battery made from the positive electrode material of the embodiment is significantly improved, the capacity retention rate is significantly improved, the impedance is significantly reduced, the 0.7C capacity retention rate and the 2C capacity retention rate are significantly improved, and the residual capacity retention rate is significantly improved, indicating that by coating the surface of the substrate with a coating material including a rare earth metal phosphate compound, the specific capacity of the positive electrode material is improved, the impedance of the battery is reduced, and the cycle stability and rate performance of the battery are improved.
[0190] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A positive electrode material, characterized in that: The positive electrode material comprises a substrate and a coating layer, wherein the substrate comprises one or more of lithium cobalt oxide, ternary materials and lithium manganese oxide; the coating layer comprises a coating material, wherein the coating material comprises a chemical formula of RE x P y O z A rare earth metal phosphate compound, wherein 3x+5y=2z, 0<x≤1, 0<y≤1, RE includes one or more of Sc, Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu; the thickness of the coating layer is A, in nm, and based on the total weight of the positive electrode material, the weight content of RE in the rare earth metal phosphate compound is B wt%, then the positive electrode material satisfies the following relationship: 10≤A / B≤30.
2. The positive electrode material according to claim 1, wherein 20≤A / B≤25; And / or, the coating layer has a thickness A nm of 2 nm to 40 nm; And / or, based on the total weight of the positive electrode material, the weight content B wt% of the rare earth metal element in the rare earth metal phosphate compound is 0.12wt%-1.4wt%; And / or, based on the total weight of the positive electrode material, the weight content of phosphorus in the rare earth metal phosphate compound is 0.01wt%-1wt%; And / or, RE includes one or more of Y, Sm, Ce, Nd, La, Sc and Lu.
3. The positive electrode material according to claim 1, wherein In the XRD spectrum of the positive electrode material, there is a characteristic peak in the range of 2θ=25°-30°; And / or, the thermogravimetric curve of the positive electrode material has a weight loss step in the range of 620°C-900°C.
4. The positive electrode material according to claim 3, wherein The weight loss range of the weight loss step is 0.05%-2%.
5. The positive electrode material according to any one of claims 1 to 3, wherein The substrate is a single crystal structure; And / or, the median particle size Dv50 of the substrate is 2 μm-18 μm, preferably 3 μm-6 μm. And / or, the average sphericity of the substrate is 0.6-1.
6. The positive electrode material according to any one of claims 1 to 3, wherein Based on the total weight of the positive electrode material, the weight content of the rare earth metal phosphate compound is 0.15wt%-4.5wt%, preferably 0.4wt%-2wt%.
7. A positive electrode sheet, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer located on one side or both sides of the positive electrode current collector, and the positive electrode active material layer comprises the positive electrode material according to any one of claims 1 to 6.
8. The positive electrode sheet according to claim 7, wherein: The median particle size Dv50 of the positive electrode material is 2 μm-18 μm; And / or, based on the total weight of the positive electrode active material layer, the weight content of the positive electrode material is 80wt%-98.5wt%; And / or, the surface density of the positive electrode sheet is 5g / cm 2 -20g / cm 2 , preferably 7g / cm 2 -18g / cm 2 ; And / or, the compaction density of the positive electrode sheet is 3.5 g / cm 3 -4.5g / cm 3 , preferably 4g / cm 3 -4.2g / cm 3 .
9. A battery, characterized in that: The battery comprises a negative electrode sheet and a positive electrode sheet, wherein the positive electrode sheet comprises the positive electrode material described in any one of claims 1 to 6 and / or the positive electrode sheet is the positive electrode sheet described in claim 7 or 8, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer located on one side or both sides of the negative electrode current collector, the negative electrode active material layer comprises a negative electrode material, and the negative electrode material comprises one or more of a silicon-based material, a carbon-based material and a silicon-carbon composite material. Preferably, the negative electrode material is a silicon-carbon composite material.
10. The battery according to claim 9, wherein: The positive electrode sheet includes the positive electrode material; And / or, based on the total weight of the negative electrode active material layer, the weight content of silicon is 1.5wt%-50wt%; And / or, the average sphericity of the negative electrode material is 0.5-1, preferably, the average sphericity of the silicon-carbon composite material is 0.5-1.
Citation Information
Patent Citations
Method for improving stability of anode material of lithium ion battery
CN102969482A
Method for lanthanum phosphate coated lithium ion battery cathode material nickel cobalt lithium manganate
CN105958054A
Coating modification method for improving performance of rich-lithium manganese-base positive electrode material
CN106784655A
Cerium phosphate coated ternary cathode material, preparation method thereof and lithium ion battery
CN109904449A
Scandium titanium lithium phosphate coated layered cobalt-free high-nickel positive electrode material and preparation method thereof
CN111987313A